DAâ€™WAH AS A MARKETING STRATEGY (STUDY ON â€œFATHIMAH COLLECTIONâ€ BUSINESS, JOMBANG) - Fatimah Nurâ€™ainani Hidayat; Sri Hartini (El-Wasathiya: Jurnal Studi Agama, 2023)
Abstract : Da'wah, in Islamic teachings, is the process of spreading good things. Even when doing business. Business must also be done well and honestly so the company becomes a blessing. Da'wah as a marketing strategy is also permissible as long as it does not go beyond Islamic law and must invite people to goodness. This was done by Fathimatuz Zahroh, the owner of the Fatima Collection business selling Muslim clothing in Jombang, who is known for preaching through his company. This study aims to see how Fatima's form of da'wah is used for her business and what marketing strategies are implemented at the Fathimah Collection. This research uses qualitative methods with field studies which will later analyze the form of da'wah and is strengthened by the marketing mix theory by Kolter & Armstrong (2016). The results of this study are the da'wah carried out by Fatima in her Fathimah Collection business, namely Bil-Lisan preaching, Bil-Qolam preaching, and Bil-Hal preaching. In contrast, the marketing mix strategy carried out by Fathimah Collection includes product selection, price setting, selection of places (place), and implementation of promotions (promotion). Keywords: da'wah, marketing strategy, marketing mix